SIFAT FISIK DAN KIMIA TANAH PADA BERBAGAI KETINGGIAN TEMPAT DI HABITAT EBONI (Diospyros celebica Bakh.) DAS SAUSU SULAWESI TENGAH - Rukmi, Rukmi; Bratawinata, Ach. Ariffien; Pitopang, Ramadhanil; Matius, Paulus (Jurnal Warta Rimba, 2017)
The commercial utilization of ebony and the encroachment of its habitat to be converted into various community necessities have led to the decline of ebony species in their natural habitat. The physical and chemical properties of soil are a vital element of the habitat for the growth of vegetation, including in the ebony species. This study aimed to investigate the physical and chemical properties of soil at various altitudes in the Sausu Watershed, Central Sulawesi.Â  This study was conducted in the Sausu watershed, Central Sulawesi, which is a natural dispersion area for ebony. Completed composite soil sampling was conducted at three altitudes, i.e., 100-<250 m asl, 250-<400 m asl and 400-550 m asl. Subsequently, the samples were analyzed at Soil Science Laboratory of Faculty of Agriculture, Universitas Tadulako. It was carried out from February to May 2015. The results indicated that the slope and back at various altitudes of the Sausu watershed have insignificant effect on the physical and chemical properties of soil in ebony habitat. The properties, including the soil texture, permeability, bulk density or soil porosity, soil chemical properties, demonstrate the acidity level of â€œsour to acidâ€. Meanwhile, the availability of organic-C, N, P, K is classified as very low, low and moderate. The criteria of CEC is moderate to high towards fertile soil, but accompanied with moderate and high C/N ratios and very low, low and high base saturation.Keywords: Diospyros celebica, the soilâ€™s physical and chemical properties, Sausu watershed.